A boccia-based adaptive physical education model for supporting gross motor skill development in students with quadriplegia - Hakim, Arif Rohman; Muryadi, Agustanico Dwi; Dwijayanti, Karlina; Santoso, Slamet; Hartanto, Sigit Fredi (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2026)
Background: Students with quadriplegia often encounter significant barriers to participation in physical education due to limited mobility and the lack of structured adaptive learning models. Despite the potential of boccia as an inclusive sport, its use as a pedagogical tool in school-based physical education remains underexplored. Objectives: This study aimed to develop and evaluate a modified boccia-based learning model to support gross motor skill development among students with quadriplegia in special education settings. Methods: A research and development (R&D) approach based on the Borg and Gall model was implemented in six stages. Participants were recruited from a special education school in Surakarta, Indonesia, involving five students in the small-group trial and 20 students in the field trial. The intervention was conducted over eight sessions. Data were collected using expert validation sheets and a modified version of the Test of Gross Motor Development–Second Edition (TGMD-2). Pre–post differences were analysed using paired-samples t-tests, and effect size was calculated using Cohen’s d. Results: The developed model demonstrated acceptable content validity (CVR = 0.50-1.00; mean = 0.60) and satisfactory reliability (r > 0.50; p < 0.05). Gross motor skill scores increased from 48.78 (pretest) to 85.78 (posttest), with a statistically significant difference (p < 0.001) and a very large effect size (d = 3.70). However, these findings should be interpreted cautiously due to the absence of a control group and the small sample size. Conclusion: The modified boccia-based learning model shows potential as a feasible and practical approach for supporting motor skill development in students with quadriplegia. Further research using controlled experimental designs is required to confirm its effectiveness.